2020
DOI: 10.1002/ajpa.24211
|View full text |Cite
|
Sign up to set email alerts
|

Paleodemographic analysis of age at death for a population of Black Sea Scythians: An exploration by using Bayesian methods

Abstract: Objectives: Studies of the demography of past populations involving deterministic life tables can be criticized for ignoring the errors of estimation. Bayesian methods offer an alternative, by focusing on the uncertainty of the estimates, although their results are often sensitive to the choice of prior distributions. The aim of this study is to explore a range of Bayesian methods for estimating age at death for a population of nomadic warriors-Scythians from the Black Sea region. Materials and methods: In tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Model life tables have been used by Gowland and Chamberlain (2005) and Gowland (2007), as have historical records (Godde et al, 2020; Godde & Hens, 2021) and modern, historical, and anthropological populations characterized through Gompertz parameters (Sasaki & Kondo, 2016a). An approach that is gaining traction is the use of a combined sample of many populations regarded as representative of preindustrial societies (Caussinus & Corgeau, 2010; Łukasik et al, 2021; Séguy et al, 2008, 2013; Séguy & Buchet, 2013). What would be best as an informative prior is the age‐at‐death distribution one is striving to obtain when examining skeletons in the first place to avoid age mimicry (Hoppa & Vaupel, 2002b; Konigsberg & Frankenberg, 1992; Love & Müller, 2002).…”
Section: Age Estimationmentioning
confidence: 99%
“…Model life tables have been used by Gowland and Chamberlain (2005) and Gowland (2007), as have historical records (Godde et al, 2020; Godde & Hens, 2021) and modern, historical, and anthropological populations characterized through Gompertz parameters (Sasaki & Kondo, 2016a). An approach that is gaining traction is the use of a combined sample of many populations regarded as representative of preindustrial societies (Caussinus & Corgeau, 2010; Łukasik et al, 2021; Séguy et al, 2008, 2013; Séguy & Buchet, 2013). What would be best as an informative prior is the age‐at‐death distribution one is striving to obtain when examining skeletons in the first place to avoid age mimicry (Hoppa & Vaupel, 2002b; Konigsberg & Frankenberg, 1992; Love & Müller, 2002).…”
Section: Age Estimationmentioning
confidence: 99%
“…There are numerous examples of Bayesian methods and inference in bioarchaeological research, including for the purposes of estimation of individual skeletal ages and paleodemographic analyses (Boldsen et al, 2002; Coqueugniot et al, 2010; DiGangi et al, 2009; Godde & Hens, 2012, 2021; Godde et al, 2020; Gowland & Chamberlain, 2002; Konigsberg & Frankenberg, 1992; Łukasik et al, 2021; Müller et al, 2002; Nagaoka & Hirata, 2007; Sasaki & Kondo, 2016; Séguy et al, 2013); estimation of sex (Konigsberg & Hens, 1998), ancestry (Rathmann et al, 2019), and stature (Konigsberg et al, 1998); paleopathological diagnosis (Boldsen, 2007; Byers & Roberts, 2003); evaluation of antemortem tooth loss (Gilmore, 2013); and dietary reconstruction (Arcini et al, 2014; Chinique de Armas et al, 2017; Stantis et al, 2020). Although many scholars may recognize the value of the analytical rigor that Bayesian approaches represent and their advantages over frequentist approaches and classical hypothesis testing, some Workshop participants suggested that a greater number of bioarchaeologists (particularly in US contexts, as Bayesian approaches are used more commonly elsewhere) may be more strongly compelled to adopt them if more bioarchaeological studies were published that explicitly demonstrate their practical utility with respect to the questions addressed (similar to Konigsberg & Frankenberg, 2013).…”
Section: Research Design and Quantitative Methodsmentioning
confidence: 99%
“…People’s health and well-being have always been negatively affected by low life expectancy, high child and young adult mortality, high interpersonal violence, and high burden of diseases generally recognized as infections . Mortality associated with known epidemics in human history was often selective with pre-existing frail health conditions and socioeconomic inequalities, but both wealthy and poor alike utilized a plethora of foods, plants, and local knowledge of their processing and admixture in efforts to improve overall health outcomes .…”
Section: Introductionmentioning
confidence: 99%